2004
DOI: 10.1016/s0277-9536(03)00397-6
|View full text |Cite
|
Sign up to set email alerts
|

‘Cultivating health’: therapeutic landscapes and older people in northern England

Abstract: While gardening is seen, essentially, as a leisure activity it has also been suggested that the cultivation of a garden plot offers a simple way of harnessing the healing power of nature (The therapeutic garden, Bantam Press, London, 2000). One implication of this is that gardens and gardening activity may offer a key site of comfort and a vital opportunity for an individual's emotional, physical and spiritual renewal. Understanding the extent to which this supposition may be grounded in evidence underpins thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
285
0
5

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(309 citation statements)
references
References 35 publications
11
285
0
5
Order By: Relevance
“…The landscape is one of the environmental factors that can affect happiness by creating evolutionary kind of feeling (Searns, 1995;Milligan et al, 2004). Hartig et al (2010) focused on the living environment around people that can shape the human mind.…”
Section: Resultsmentioning
confidence: 99%
“…The landscape is one of the environmental factors that can affect happiness by creating evolutionary kind of feeling (Searns, 1995;Milligan et al, 2004). Hartig et al (2010) focused on the living environment around people that can shape the human mind.…”
Section: Resultsmentioning
confidence: 99%
“…The therapeutic value of community gardening as a physical activity has been recognised for creating opportunities for ecological engagement and 'emotional, physical and spiritual renewal' and for contributing to the health and wellbeing of the elderly. 37 Food gardening as a leisure activity is associated with building stronger relationships and social capital at a local level. 38 A study of allotment gardens in Barcelona, Spain, found that, beyond providing a source of food, allotment gardening also makes use of the skills and knowledge brought by retirees from rural areas, such that the community garden was 'a space of physical and psychological well-being and communion with a former rural life that they had to abandon when migrating towards the industrial centres'.…”
Section: Box 1 Life Cycle Assessment In the Agrifood Sectormentioning
confidence: 99%
“…African PUA development is mainly focused on food and fuel production, which relates to alleviating hunger and poverty (Ellis & Sumberg, 1998;Lee-Smith, 2010). European PUA emphasizes the ecological values of green spaces and their associated social values such as recreation and therapeutic treatment (City Farmer, 2007;Holland, 2004;Milligan et al, 2004). Although economy and production have been much liberalized after economic reform, agriculture is strongly supported and controlled by the government to a large extent especially in Beijing and most inland cities where municipal governments are highly dominated even in economic development (Yang, Cai, & Ottens, Sliuzas, 2013).…”
Section: Introductionmentioning
confidence: 99%